Digital Holography and Three-Dimensional Imaging 2017
DOI: 10.1364/dh.2017.m4b.1
|View full text |Cite
|
Sign up to set email alerts
|

Application of wavefront printer-from static 3D visualization to projection-type holographic display-

Abstract: Wavefront printer can record arbitrary designed wavefront not only for static 3D visualization but also for holographic screen to be used on projection-type holographic display. Some applications related to the wavefront printer are introduced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…An example how this can be utilized to design highly accurate recording schemes with photopolymers is given in [78]. For master vHOE recording holographic printer designs were published in the last years that are able to deal with photopolymers [79][80][81][82][83][84][85][86][87]. The start of this was also triggered by building recorders for holographic optical data storage [88].…”
Section: Towards a Value Chain For A Volume Hologram Industrymentioning
confidence: 99%
See 1 more Smart Citation
“…An example how this can be utilized to design highly accurate recording schemes with photopolymers is given in [78]. For master vHOE recording holographic printer designs were published in the last years that are able to deal with photopolymers [79][80][81][82][83][84][85][86][87]. The start of this was also triggered by building recorders for holographic optical data storage [88].…”
Section: Towards a Value Chain For A Volume Hologram Industrymentioning
confidence: 99%
“…For digitally printed vHOEs recorded with Bayfol ® HX film, each pixel is recorded with a different optical function. Using a digital holographic projector, larger display size as well as larger FOV has been demonstrated as an example of a transparent screen [79,83]. Using a laser projector, a collimating lens, a diffuser and a free space optical combiner recorded as vHOE in Bayfol ® HX film the authors demonstrated the correction of astigmatism and optical aberrations even for different viewer distances [99] as it could be used in HMD.…”
Section: Application Of Bayfol ® Hx Film In Academia and Industrymentioning
confidence: 99%